ACCIDENTAL PENILE FRACTURE CAUSED BY SELF-INVOLVEMENT IN THE ABSENCE OF SEXUAL ACTIVITY: A CASE REPORT - Falamy, Ryan; Mirza, Hendy; Afriansyah, Andika (Indonesian Journal of Urology, 2024)
Objective: This study aims to present a case of accidental penile fracture without sexual activity. Case(s) Presentation: A 40-year-old guy was sent to our emergency center nine hours prior to admission with oedema and lack of tumescence on the penis. There were no records of sexual activity or masturbation. The patient was treated for a hematoma and a fracture. The patient raised no complaints during his one-week and two-month follow-up visits after the procedure. Discussion: A urological emergency involving penile fracture is uncommon. It is important to avoid unnecessary delays in obtaining medical help. In the current case study, with urgent surgical intervention, corporal tears were repaired. Recent research recommends prompt surgical treatment of penile fractures, as this appears to be associated with fewer complications and better results. Conclusion: A penile fracture that requires immediate surgical treatment can preserve erectile and voiding function. Keyword: Penile fracture, urological emergency, surgical treatment.